Passive Communication - Style and Its Impact on Teachers’ Professional Development - Bîrsan, Elena (Didactica Danubiensis, 2025)
Abstract Objectives: This study examines educational communication, with a particular focus on the defining traits of passive communication and its impact on personal and psychological crises that undermine self-esteem. Prior Work: The research extends contemporary understanding of passive communication, identifying it as a significant barrier to teachers’ professional development. Approach: Employing a scientifically grounded analytical framework, the study investigates the dynamics of educational communication and the psychological mechanisms influencing teachers’ communicative behaviors. Results: The findings reveal the distinctive features of educational communication and systematically illustrate how passive communication distorts teachers’ interaction patterns and negatively affects self-perception. The study identifies key barriers associated with the adoption of a passive communicative style in educational environments. Implications: The study highlights the formative role of communicative behavior in shaping teachers’ professional identity and their capacity to foster self-esteem, both personally and among the beneficiaries; it delineates the behavioral profile of passive communicators, and it examines the professional and relational consequences associated with this communicative style. Value: This research clarifies the concept of educational communication and emphasizes its significance for the professional development of teaching staff; additionally, it reveals behavioral deficiencies and dysfunctions that may arise from the prolonged adoption of a passive communication style.